KINERJA ORGANISASI PENGELOLA TINGKAT MASYARAKAT DALAM PEMANFAATAN DAN PEMELIHARAAN HASIL PROGRAM SANIMAS DI KELURAHAN KAPALO KOTO KOTA PADANG - Hafizhah Hafizhah (Universitas Lambung Mangkurat, 2020)
This research is motivated by environmental pollution because many people do not yet have access to proper domestic wastewater sanitation. Kapalo Koto Village is one of the priority villages in handling sanitation in Padang City. The results showed that of the four variables proposed by Wibowo, it can be concluded that the Performance of Community Level Management Organizations in the Utilization and Maintenance of the Results of the SANIMAS Program in the Kapalo Koto Village Padang City has not yet reached its maximized. Utilization and maintenance activities of the SANIMAS Program result in the Kapalo Koto Village experienced several obstacles. Caused by several indicators that have not been maximized, such as the capability of low Community Level Management Organizations, sources of funding from beneficiary community contributions for program maintenance and development are not collected. The implementation of utilization and maintenance activities is still not routinely carried out. Continued monitoring is not conducted regularly and evaluation activities are not carried out annually. However, if seen from the benefits generated by the SANIMAS Program it has an impact on reducing pollution to the residential environment, thereby causing an increase in the level of public health. Keywords: Performance, Management Organizations, SANIMAS Program